The Silent Takeover - Hertz, Noreena (HARPER, 2003)
Of the world's 100 largest economies, 51 are now corporations, only 49 are nation-states. The sales of General Motors and Ford are greater than the gross domestic product of the whole of sub-Saharan Africa, and Wal-Mart now has a turnover higher than the revenues of most of the states of Eastern Europe. Yet few of us understand fully the growing dominance of big business.